The Construction of Customary Law In The Bedolan Tradition in The Wedding Ceremony of Banjararjo People Village, Ayah Subdistrict, Kebumen City Based on Islamic Law - Rohmah, Azizatu (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
A wedding ceremony is a very important event for Javanese people. In a wedding, there are two receptions held. The activities are organized by the bride's family and the groom's family. Each activity contained in the wedding has a different ceremonial procession. This ceremony sticks to the rule book (pakem), the procedure or implementation of this tradition not only shows the value of beauty but also contains the philosophical meaning of each series of traditional ceremonies. The purpose of writing this scientific essay is to explore and examine the nature of the wedding procession based on factual events held in Banjararjo Village, Ayah Subdistrict, Kebumen Regency and see the phenomenon based on Urf review. The research method used is fieldwork, observation, and interviews, with a normative juridical approach with Urf theory. The results of this study indicate that the marriage tradition in Banjararjo Village is very close in upholding the existence of Javanese traditions and culture in the marriage procession, one of the series of ceremonies is the Bedolan tradition or commonly referred to as Ngunduh Mantu, this is in line with the theory of al-adah muhakkamah which has been going on dark ancestors.